Should we keep performing electrical cardioversion in atrial fibrillation/flutter?. (14th October 2021) - Menezes Fernandes, R; Mota, T.F; Costa, H.A; Espirito Santo, M; Bento, D; Candeias, R; Mimoso, J; Jesus, I
Abstract: Introduction: Atrial fibrillation (AF) and atrial flutter (AFL) are frequently diagnosed arrhythmias in the outpatient setting or in the Emergency Department. Electrical cardioversion (EC) is a therapeutic option when a rhythm control strategy is pursued. Purpose: To evaluate the clinical outcomes of patients with AF/AFL referred to EC and to analyse the procedures' complications. Methods: We conducted a retrospective study enrolling patients with AF/AFL referred to EC in our Cardiology Department, from September 2011 to September 2020. Clinical characteristics, echocardiographic studies and follow-up data were analysed. Primary endpoint was the incidence of ischemic stroke during follow-up. Results: A total of 719 patients were referred to EC during the 9-year period, with a median age of 67 years-old and 70, 4% male predominance. Most patients were cardioverted in an outpatient setting (60, 6%) and 21% had AFL. 62, 1% had persistent AF/AFL, 19, 6% presented with first diagnosed AF/AFL and 17, 2% had paroxysmal episodes. EC was successfully performed in 93, 2% and 0, 3% had major non-fatal immediate complications. Arterial hypertension was present in 57, 3% of patients, 20, 4% had diabetes, 34, 6% were obese, 13, 3% mentioned alcohol consumption and 6, 3% had sleep apnea. Previous stroke was diagnosed in 6, 8% and 19% had ischemic heart disease. Left ventricular (LV) ejection fraction (LVEF) was preserved in 66, 7%. Median CHA2DS2-VASc score was 2, 0 and 89, 8% were anticoagulated (75, 7% with non-vitamin K antagonist oral anticoagulants). Antiarrhythmic therapy was prescribed in 85% and 64, 5% maintained sinus rhythm one-year after EC. After EC, it was documented complete reversal of LV systolic dysfunction in 46, 3% of patients with previously reduced LVEF, confirming the diagnosis of arrhythmia-induced cardiomyopathy (AIC). During a median follow-up of 1355 days, ischemic stroke occurred in 4, 8%, but only 5 patients had an embolic event in the first week after EC (0, 7% stroke rate at one week, the same at one month). AIC was associated to a lower rate of cardiovascular death (3, 8% vs 25, 5%; p=0, 002), comparing to patients who did not recover LV function. Conclusion: EC is a safe procedure, with a very low rate of immediate and embolic complications. AIC was diagnosed in 46, 3% of patients with previously reduced LVEF and it was associated with a significantly lower rate of CV death. EC should be considered to relieve patients' symptoms and when there is suspicion of AIC. Funding Acknowledgement: Type of funding sources: None.